2004
DOI: 10.1890/04-0463
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal and Social Attraction Affect Colony Selection and Dynamics of Lesser Kestrels

Abstract: We studied the mechanisms that regulate colony dynamics in a Spanish population of Lesser Kestrels, using eight years of data from banded individuals in 494 colony-years. Colony growth was positively related to breeding success at the colony the year before. However, individuals of all dispersal statuses, i.e., adult and first-breeding philopatric and immigrant birds, significantly contributed to changes in colony size, indicating an important effect of dispersal on colony dynamics via colony quality. Given th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 62 publications
2
93
0
2
Order By: Relevance
“…Given the lack of temporal autocorrelation, it may not be surprising that we failed to find support for public information as being important for breeding dispersal decisions, although we acknowledge our study may have been too short to reliably estimate temporal autocorrelation of reproductive success. It is possible that other cues not evaluated here, but suggested conveying public information on habitat quality, such as conspecific density (Stamps 2001;Doligez et al 2004;Serrano et al 2004) or feeding rate (Pärt and Doligez 2003), may influence dispersal behavior of the red-backed shrike.…”
Section: Reproductive Performancementioning
confidence: 99%
“…Given the lack of temporal autocorrelation, it may not be surprising that we failed to find support for public information as being important for breeding dispersal decisions, although we acknowledge our study may have been too short to reliably estimate temporal autocorrelation of reproductive success. It is possible that other cues not evaluated here, but suggested conveying public information on habitat quality, such as conspecific density (Stamps 2001;Doligez et al 2004;Serrano et al 2004) or feeding rate (Pärt and Doligez 2003), may influence dispersal behavior of the red-backed shrike.…”
Section: Reproductive Performancementioning
confidence: 99%
“…In spite of its strong connection with population dynamics and animal conservation, behavior has seldom been taken into account in models of extinction and species-habitat relationships (Reed, 1999). The use of conspecifics as cues during the habitat selection process is a widespread strategy that may promote animal aggregations at traditionally occupied sites (Serrano et al, 2004;Sergio and Penteriani, 2005). On the other hand, antagonistic interactions between neighbors may preclude territory establishment, since high intraspecific densities may increase competition for resources (Newton, 1998;Carrete et al, 2006;Serrano and Tella, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This relationship would be expected if either an increase in murres required an increase in nesting locations (a spillover effect) or if the increase in murres provided positive public information (Valone & Templeton 2002), encouraging more conspecifics to settle via social attraction (Serrano et al 2004). Testing specific social attraction hypotheses, such as the influence of differential attendance of individuals (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, blacklegged kittiwakes Rissa trydactyla evaluate the quality of potential breeding sites by observing the numbers and reproductive success of presumably unrelated birds breeding there (public information, see review in Valone & Templeton 2002) and choose whether or not to settle accordingly (Danchin et al 1998). Similarly, very low density Arctic skua Stercorarius parasiticus colonies attract fewer recruits than do high density, productive colonies (Phillips et al 1998), whereas only colony size, not reproductive success, was found to influence immigration in lesser kestrels Falco naumanni (Serrano et al 2004). However, these mechanisms operate only when a colony is already occupied.…”
Section: Introductionmentioning
confidence: 96%